Occurrence of Escherichia coli in Fresh and Frozen Frog Legs: Implications for Quality Assurance of Export-Oriented Fishery Products - Muhammad Sazili; Marisha Ramadanti Setiawan; Widya Pitaloka; Riya Liuhartana Nasyiruddin Fuhrmann; Irem Kılınç (CV. Media Inti Teknologi, 2026)
Background: Frog legs are an important Indonesian export commodity that must meet strict food safety standards. Among microbiological hazards, Escherichia coli is widely recognized as an indicator of faecal contamination and poor hygienic practices during processing.Aim: This study aimed to determine the occurrence of E. coli in fresh and frozen frog leg products and evaluate the effectiveness of quality assurance measures applied throughout the production chain.Methods: The study was conducted at the Fishery Product Quality Control and Inspection Agency (BPPMHKP) Palembang, Indonesia, from April to May 2025. Detection of E. coli was performed using the Most Probable Number (MPN) method according to Indonesian National Standard SNI 2332.1:2015. The procedure included enrichment in Lauryl Tryptose Broth (LTB), presumptive testing in EC Broth, and confirmation on Eosin Methylene Blue (EMB) Agar.Results: Several samples showed positive reactions during the enrichment and presumptive stages, suggesting the presence of coliform bacteria. However, no characteristic metallic-green colonies of E. coli were observed on EMB Agar during confirmation. All fresh and frozen frog leg samples had contamination levels below 3 MPN/100 mL. No significant difference in E. coli contamination was detected between the two product categories.Conclusion: Fresh and frozen frog legs complied with microbiological safety requirements and were free from confirmed E. coli contamination. The findings indicate that quality assurance systems, including certified raw material sourcing, Good Manufacturing Practices (GMP), Sanitation Standard Operating Procedures (SSOP), and cold-chain management, effectively maintained product safety and quality for export purposes.